The Implementation of Art Drawing Therapy in Patient Nn. F with Schizophrenia and Primary Problem of Suicide Risk at RSKD Duren Sawit - Jeni Nur Aini; Jesika Pasaribu (Jurnal Keperawatan Jiwa, 2026)
Severe mental disorders such as schizophrenia are often accompanied by depressive symptoms, hallucinations, and an increased risk of suicide. Patients with limited verbal communication require safe and supportive non-pharmacological interventions to express their emotions. Art Drawing Therapy is an art-based therapeutic approach that facilitates non-verbal emotional expression through drawing activities. This study aimed to describe the implementation of Art Drawing Therapy in a patient with schizophrenia whose primary problem was suicide risk at RSKD Duren Sawit. The method used was a case study with a psychiatric nursing care approach. Art Drawing Therapy was conducted in five sessions, each lasting 30–45 minutes. The results showed an improvement in the patient’s psychological condition, indicated by a reduction in suicidal ideation, decreased self-harm behavior, improved affective stability, and enhanced ability to express emotions adaptively. Art Drawing Therapy proved to be an effective and applicable psychiatric nursing intervention in reducing suicide risk among patients with schizophrenia.